Applications of asphalt concrete overlay on Portland cement concrete pavement. (20th December 2020) - Zhao, Zifeng; Guan, Xin; Xiao, Feipeng; Xie, Zuping; Xia, Ping; Zhou, Qingyue
Highlights: Pre-overlay treatment plays and indispensable role in asphalt overlay construction. Partial depth repair for mid-severity joints is proved to be beneficial. Advantages and disadvantages of eight common interlayers are presented. Overlay thickness, base condition, asphalt binder type and traffic volume are key factors. Additional overlay thickness can retard the development of reflection cracks. Abstract: Being one of the most common method to restore the structural and functional capabilities for distressed Portland cement concrete pavement, the practice of asphalt concrete overlay dates to the mid-20th century and even earlier. Workmanships and techniques adopted for the application had been widely researched. In view of the increasing demand for pavement rehabilitation, this work summarizes the following: firstly, the basic procedures for asphalt concrete overlay construction by considering about 100 papers published since 1950 to till date. Secondly, the overlay thickness design methods including the thickness deficiency-based approach and thickness analytical-based approach. Thirdly, the advantages and disadvantages of various kinds of interlayers adopted in engineering fields. Fourthly, the possible factors that would affect the propagation of reflection cracks, such as traffic volume, overlay binder type, base condition, etc. Fifthly, the possible construction alternatives in terms of construction period and traffic closure. Overall, by employing analytical-based methods, this review brings to light that additional overlay thickness can reduce the fatigue stress, thermal stress, and traffic loading stress at the bottom of the overlay, resulting in overall smaller stress level. Moreover, additional overlay thickness also contributes to the decrease in daily reflection crack length according to Paris' law. Further, this review stresses the indispensable role for pre-overlay treatment and recommends careful investigations during overlay construction.